Respuesta :

Answer:

f^-1(x) = (x +5)/3

also = 1/3 x + 5/3

Step-by-step explanation:

Just to be clear, the ^-1 has nothing to do with negative exponents. It just unfortunately looks the same as a negative exponent.

Anyway, there's three basic steps. First write y instead of f(x). Then switch the x and y. Then solve for y.

f(x) = 3x - 5

write y in place of f(x).

y = 3x - 5

SWITCH x and y.

x = 3y - 5

SOLVE for y.

-3y + x = -5

-3y = -x - 5

y = (-x - 5)/-3

y = (x + 5)/3

OR

y = (1/3)x + 5/3

f^-1(x) = 1/3 x + 5/3